Efficacy and tolerability of paclitaxel, ifosfamide, and cisplatin as a neoadjuvant chemotherapy in locally advanced cervical carcinoma - Scandurra, Giuseppa (J Gynecol Oncol, 2015)
OBJECTIVE: To evaluate the efficacy and tolerability of a neoadjuvant paclitaxel, ifosfamide, and cisplatin chemotherapy in patients with locally advanced cervical carcinoma. METHODS: Patients with histologically confirmed locally advanced cervical carcinoma, aged ≥18 years, were treated with intravenous ifosfamide 5,000 mg/m(2) and mesna 5,000 mg/m(2), on day 1; intravenous paclitaxel 175 mg/m(2) and cisplatin 75 mg/m(2), on day 2; every 3 weeks for three cycles. Following chemotherapy, operable patients underwent radical hysterectomy and pelvic lymphadenectomy, and, if necessary, adjuvant radiotherapy. RESULTS: One hundred fifty-two patients with median age 53 years (range, 24 to 79 years), FIGO stage IIB in 126 (89%), were treated with chemotherapy for median 3 cycles (range, 1 to 3). Treatment was delayed or withdrawn in 23 patients (15%). One hundred thirty-nine patients (91%) underwent surgery. Postchemotherapy pathological complete response rate was 18% (25 patients). Postoperative radiotherapy was administered in 100 patients (72%). The 5-year overall survival and progression-free survival were 87.3% (95% confidence interval [CI], 84.5 to 90.3) and 76.4% (95% CI, 73.5 to 79.5), respectively. CONCLUSION: Neoadjuvant paclitaxel, ifosfamide, and cisplatin chemotherapy was feasible and effective in the treatment of locally advanced cervical carcinoma patients with older age and more advanced disease stage than reported in previous studies. Hematological and renal toxicity could be carefully prevented.